Effect Social Piety affect the Relationship between Public Service Quality and Community Satisfaction - Andespa, Wira; Puteri, Hesi Eka (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
The standard of an institution's public services has a big impact on its policy and direction in providing services. This study aims to compute the moderating impact utilizing social piety factors, that is, interaction patterns that elucidate the relationship between public service quality and public contentment. In this study, SEM PLS analysis was performed using the Warppls 8.0 analytical tool. A total of 161 respondents who were employed by the Bukittinggi City Dukcapil Service were selected via an incidental sampling technique. Research results show that knowledge management (KM) is positively impacted by public service quality, with a Î² value of 0.79 and a R^2 value of 0.62, both less than 0.05. This demonstrates that 62% of the influence of public services on community happiness may be attributed to this. The association between public enjoyment and the caliber of public services is somewhat mediated by the social piety variable. With a moderating contribution of KS to the influence of KPS on KS, the moderation effect coefficient value of 0.49 and the P-value of 0.01 are both less than 0.5. The R^2 value of 0.68 indicates an influence.